Recent insights about autophagy in pancreatitis - Xiaowen Ma; Shaogui Wang; Wen-Xing Ding; Hong-Min Ni; Sydney Kim (eGastroenterology)
Acute pancreatitis is a common inflammatory gastrointestinal disease without any successful treatment. Pancreatic exocrine acinar cells have high rates of protein synthesis to produce and secrete large amounts of digestive enzymes. When the regulation of organelle and protein homeostasis is disrupted, it can lead to endoplasmic reticulum (ER) stress, damage to the mitochondria and improper intracellular trypsinogen activation, ultimately resulting in acinar cell damage and the onset of pancreatitis. To balance the homeostasis of organelles and adapt to protect themselves from organelle stress, cells use protective mechanisms such as autophagy. In the mouse pancreas, defective basal autophagy disrupts ER homoeostasis, leading to ER stress and trypsinogen activation, resulting in spontaneous pancreatitis. In this review, we discuss the regulation of autophagy and its physiological role in maintaining acinar cell homeostasis and function. We also summarise the current understanding of the mechanisms and the role of defective autophagy at multiple stages in experimental pancreatitis induced by cerulein or alcohol.